2022
DOI: 10.1038/s41467-022-28160-8
|View full text |Cite
|
Sign up to set email alerts
|

Global climate-driven trade-offs between the water retention and cooling benefits of urban greening

Abstract: Urban greening can potentially help mitigate heat-related mortality and flooding facing the >4 billion urban population worldwide. However, the geographical variation of the relative combined hydrological and thermal performance benefits of such interventions are unknown. Here we quantify globally, using a hydrological model, how climate-driven trade-offs exist between hydrological retention and cooling potential of urban greening such as green roofs and parks. Using a Budyko framework, we show that water r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 65 publications
(69 reference statements)
1
16
0
2
Order By: Relevance
“…We used the aridity level (i.e. wetness index), which has been found to be a controlling factor for urban heat (Zhang et al 2022) and the performance of UG in water retention and cooling (Ibsen et al 2021, Cuthbert et al 2022, to classify the US cities into dry and non-dry regions. Overall, we found that RWH has a higher potential for long-term urban water management in non-dry regions than in dry regions, whereas UG can provide a greater opportunity for carbon sequestration and cooling in dry regions, and even more if supported by RWH and other irrigation water sources.…”
Section: Discussionmentioning
confidence: 99%
“…We used the aridity level (i.e. wetness index), which has been found to be a controlling factor for urban heat (Zhang et al 2022) and the performance of UG in water retention and cooling (Ibsen et al 2021, Cuthbert et al 2022, to classify the US cities into dry and non-dry regions. Overall, we found that RWH has a higher potential for long-term urban water management in non-dry regions than in dry regions, whereas UG can provide a greater opportunity for carbon sequestration and cooling in dry regions, and even more if supported by RWH and other irrigation water sources.…”
Section: Discussionmentioning
confidence: 99%
“…Green space in, and surrounding settlements, along with proximity to the coast appeared to protect informal settlements from the worst UHIs. Green space has a cooling effect both through shading and evapotranspiration (Aflaki et al 2017), although the cooling potential from evapotranspiration is upper bounded by high humidity in the tropics (Yu et al 2018;Manoli et al 2019;Cuthbert et al 2022). Meanwhile, large water bodies, including oceans and lakes, have a cooling effect due to the temperature differential between land and water producing cool onshore breezes during the day (Bonan 2002;Adams & Smith 2014;Cai et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than assuming benefits a priori, projects should develop a clear assessment of the mitigation and adaptation benefits to be achieved, and of the climate risks and impacts that can be avoided or addressed. For example, tree planting or “green roofing” in cities as a cooling strategy is effective (more at daytime than at nighttime), but the evidence for larger scale cooling effects remains inconclusive (Bowler et al 2010 ; Cuthbert et al 2022 ). Similarly, active reforestation to rehabilitate degraded rural landscapes can increase the provision of specific ecosystem services, including climate mitigation and soil erosion control, but may not necessarily be a cost-effective strategy compared to natural revegetation (Meli et al 2017 ; Honey-Rosés et al 2018 ).…”
Section: Toward Nature-inspired Justicementioning
confidence: 99%